Fiscal equalisation - Blöchliger, Hansjörg (OECD Publishing, 2008)
By Hansjörg Blöchliger and Claire Charbit Fiscal equalisation is a transfer of fiscal resources across jurisdictions to offset disparities in revenue raising capacity or public service cost. It covers on average 2.5% of GDP or 5% of total government expenditure across OECD countries. Equalisation reduces fiscal disparities by two-thirds on average and in some countries levels them virtually out. Strong equalisation comes at a price: on average, around 70% of a jurisdiction's additional tax income must be dedicated to an equalisation fund. The equalisation rate is generally higher for jurisdictions with low fiscal capacity, reducing their tax effort and likely to slow down regional economic convergence. Cost equalisation is larger than revenue equalisation in terms of GDP despite smaller cost disparities, pointing at inefficiencies in the distribution formulae. Fiscal equalisation can be pro-cyclical but most countries succeed in reducing fluctuations of entitlements, sometimes at the cost of sub-central budget needs. Fiscal equalisation is very country specific, and data and analysis must be taken with care